Pengaruh Digital Marketing, Word of Mouth dan Persepsi Kemudahan terhadap Keputusan Penggunaan dalam Aplikasi Mobile Banking Livin by Mandiri di PT Bank Mandiri (Persero) Tbk KCP Cikarang Jababeka - Jayanty, Maghdina; Handayani, Langgeng Sri (Jurnal Ilmiah Global Education, 2024)
PT Bank Mandiri (Persero) is a banking company that was restructured from several state banks, namely Bumi Daya Bank, State Trade Bank, Export Import Bank and Indonesian Development Bank. This research, entitled the influence of digital marketing, word of mouth, and perceived ease of use on usage decisions in the Livin by Mandiri mobile banking application, is quantitative research with a survey approach via questionnaires. The population in this study were customers of Bank Mandiri KCP Cikarang Jababeka. The sample used in this research was 100 respondents. The sampling used in this research used a simple random sampling technique, namely a technique for taking sample members from the population randomly without paying attention to the overall level. The results of the research show that digital marketing does not have a significant influence on the decision to use Livin by Mandiri mobile banking for Bank Mandiri KCP Cikarang Jababeka customers, word of mouth has a significant influence on the decision to use Livin by Mandiri mobile banking for Bank Mandiri customers KCP Cikarang Jababeka, perception of ease of use significant influence on the decision to use Livin by Mandiri mobile banking for Bank Mandiri KCP Cikarang Jababeka customers.